Profit sharing and relative consumption - Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2012)
Traditionally, it has been argued that profit sharing can increase employment and welfare because it lowers marginal labour costs without reducing total cost or labour income. In this paper, we show that profit sharing can also represent a Pareto-improvement if labour supply is excessive due to relative consumption effects. Mandatory profit sharing reduces wages. If the rise in profit income keeps total income constant, profit sharing will have no income but only a substitution effect. Since labour supply is excessive, profit sharing constitutes a Paretoimprovement.
Keywords: D62; J22; J33; 330; Labour supply; Profit sharing; Relative consumption; Status concerns; Erfolgsbeteiligung; Arbeitsangebot; Konsuminterdependenz; Pareto-Optimum; Theorie